Racer: a simulated environment driving simulator to investigate human driving skill - Hisham, A.A.B. (Springer Verlag, 2017)
The identification and the quantification of human skill is one of the major characteristics to be considered in designing an algorithm for Human Adaptive Mechatronics (HAM) application. This paper focuses on studying the Racer software, as well as the relationship of data gained and the simulated environment. The fact that Racer is chosen as the tool is described. This paper discusses the details about the software used; Racer as the driving simulator environment during the experiment. The experimental setup, data extraction process and data conversion are explained further in this paper. The experimental results meet the purpose of data collection which provides variety set of data, including many options for cars and tracks. As a conclusion, Racer is a suitable software to be used. The utmost important, the further study of this research will help during the development of car assistance system. © Springer Nature Singapore Pte Ltd. 2017.